Tom Foley : the man in the middle - Bird, Kenton, 1954-; Pierce, John C. (Congressional leaders., 2023)
"Thomas S. Foley, a Democratic representative from the traditionally Republican region of eastern Washington, served in Congress for thirty years, from 1964 to 1994. In 1989 he became the first Speaker of the US House of Representatives from a district west of Texas. His experience as a Democrat from a Republican district contributed to his strong commitment to bipartisanship and institution-building. His leadership came to an end with the Newt Gingrich-led Republican "revolution" that ushered in an era of ideological polarization and partisanship. Speaker Tom Foley is a political biography of this important but often ignored and overlooked figure in modern congressional history. In addition to examining the story of Foley's service as Speaker of the House, R. Kenton Bird and John C. Pierce address key themes that emerge from placing his career in the context of both his own life story and congressional politics in the late twentieth century. What emerges is the story of a leader whose strongly held political values motivated him to sustain a vibrant and responsive House of Representatives as an institution, but left him unsuited for the polarized and strident political environment that emerged in the early 1990s, a climate fueled by talk radio and other conservative media and successfully exploited by Gingrich and his fellow partisans. Though he was a reformed in the 1970s, by the 1990s he was seen as part of an "old guard" holding back the House from further reform. His defeat marked a seismic transition in the landscape of American politics"--